(untitled) (Eurasian Research Bulletin, 2023)
This article analyzes the sources and literature related to the ambassador and his personality in the study of Khiva Khanate and Russian diplomatic relations, and you can see to what extent the rules of diplomatic etiquette were observed in the Khanate